2009
DOI: 10.1038/bmt.2009.174
|View full text |Cite
|
Sign up to set email alerts
|

Decisions to register for the National Marrow Donor Program: rational vs emotional appeals

Abstract: Little research has examined how the content of health communications regarding the need for BM and stem cell donation affects the intentions and attitudes of potential National Marrow Donor Program (NMDP) donors. This study used an experimental design to test the hypothesis that an emotional appeal (EA) to potential donors would lead to higher rates of NMDP registration than a rational appeal (RA). Participants were randomly assigned to receive either a RA or an EA and then asked if they would (1) register wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…In numerous countries including Turkey, the main barriers to stem cell donation are social, economic, and cultural factors. 8,16,18,19,[23][24][25] In the present study, > 60% medical students indicated that media affected their willingness to donate stem cells (Table 4). To date, media such as television, radio, and newspapers have been the primary sources of information about organ donation and transplantation 14 Media reports may positively affect public attitudes about HSCT and donation in Turkey.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In numerous countries including Turkey, the main barriers to stem cell donation are social, economic, and cultural factors. 8,16,18,19,[23][24][25] In the present study, > 60% medical students indicated that media affected their willingness to donate stem cells (Table 4). To date, media such as television, radio, and newspapers have been the primary sources of information about organ donation and transplantation 14 Media reports may positively affect public attitudes about HSCT and donation in Turkey.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, medical students were of specific interest because this group is likely to be informed about health issues in ways that are not representative of the general population. 16 The study participants were from all geographic regions of Turkey and had different levels of previous health knowledge. Therefore, these students may be representative of the younger generation in Turkey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies investigated how or whether or if factors such as age, ethnicity, gender, knowledge, demographics, cultural influences or attitudes, and fears can affect the decision to donate [7,[17][18][19].…”
mentioning
confidence: 99%
“…Another study in the USA tested the hypothesis that an emotional appeal would lead to higher registration rates than a rational appeal [18]. The participants, 102 medical students, were divided into two groups.…”
mentioning
confidence: 99%